Effect of broccoli (Brassica oleracea) florets and stems as a fat replacer on the physicochemical and sensorial properties of chicken patties - Wei-Ai, Wei-Ai; Faridah, Mohd Razali; Asyrul-Izhar, Abu Bakar; Ab Aziz, Muhamad Faris; Kumar, Pavan; Sazili, Awis Qurni; Ismail-Fitry, Mohammad Rashedi (Journal of Meat Science, 2025)
This study aimed to evaluate the effects of replacing animal fat with various levels of broccoli (0, 25, 50, 75, and 100%) on the physicochemical and sensory properties of chicken patties. Fresh broccoli florets and stems were blanched and minced before being added to the patties' formulation, and all samples were analysed for their physicochemical and sensorial properties. The highest significant (P
Keywords: broccoli; fat replacers; healthier patties; low-fat chicken patties; meat products